The voluntary medical male circumcision Site Capacity and Productivity Assessment Tool (SCPT): An innovative visual management tool to optimize site service delivery - Emmanuel Njeuhmeli; Michel Tchuenche; Marjorie Opuni; Peter Stegman; Matt Hamilton; Steven Forsythe; Felix Nhaduco; Francisco Zita; Nuno Gaspar; Jotamo Come (Public Library of Science (PLoS), 2022)
Given constrained funding for HIV, achieving global goals on VMMC scale-up requires that providers improve service delivery operations and use labor and capital inputs as efficiently as possible to produce as many quality VMMCs as feasible. The Voluntary Medical Male Circumcision Site Capacity and Productivity Assessment Tool (SCPT) is an electronic visual management tool developed to help VMMC service providers to understand and improve their site's performance. The SCPT allows VMMC providers to: 1) track the most important human resources and capital inputs to VMMC service delivery, 2) strategically plan site capacity and targets, and 3) monitor key site-level VMMC service delivery performance indicators. To illustrate a real-world application of the SCPT, we present selected data from two provinces in Mozambique-Manica and Tete, where the SCPT was piloted We looked at the data prior to the introduction of SCPT (October 2014 to August 2016), and during the period when the tool began to be utilized (September 2016 to September 2017). The tool was implemented as part of a broader VMMC site optimization strategy that VMMC implementers in Mozambique put in place to maximize programmatic impact. Routine program data for Manica and Tete from October 2014 to September 2017 showcase the turnaround of the VMMC program that accompanied the implementation of the SCPT together with the other components of the VMMC site optimizatio strategy. From October 2016, there was a dramatic increase in the number of VMMCs performed. The number of fixed service delivery sites providing VMMC services was expanded, and each fixed site extended service delivery by performing VMMCs in outreach sites. Alignment between site targets and the number of VMMCs performed improved from October 2016. Utilization rates stabilized between October 2016 and September 2017, with VMMCs performed closely tracking VMMC site capacity in most sites. The SCPT is designed to address the need for site level data for programmatic decision-making during site planning, implementation, monitoring and evaluation. Deployment of the SCPT can help VMMC providers monitor the performance of VMMC service delivery sites and improve their performance. We recommend use of the customized version of this tool and model to the need of other programs.